Engineering of E. coli for increased production of L-lactic acid - Tengku Zainal Mulok, Tengku Elida; Chong, Mei Ling; Shirai, Yoshihito; Abdul Rahim, Raha; Hassan, Mohd Ali (Academic Journals, 2009)
An over-expressed L-ldh gene derivative of Escherichia coli BAD-ldh was developed. L-ldh gene from Enterococcus facelis KK1 consisted of an open reading frame of 954 bp encoding 316 amino acids. L-ldh gene was cloned into pBAD vector and transformed into E.coli SZ85 by electroporation. SDS-page and western blotting method confirmed the presence of recombinant L-LDH enzyme with the approximate size of 40kD. The activity of L-lactate dehydrogenase was achieved at 170 U ml¯¹. E.coli BAD85 was found to produce 0.62 g l¯¹ of lactic acid from 1 g 1¯¹ of fructose in 24 h. L-ldh gene from was successfully transformed into E.coli SZ85 with the maximum production of L-lactic acid at 0.62 g l¯¹.